La población del Sureste durante los siglos oscuros (IV-X) - González Blanco, Antonino (Antigüedad y Cristianismo, 1998)
This study defines some of the forces which changed the distribution of the population in the region of Murcia in the centuries of late antiquity. Here are described the causes of the insecurity that existed from the middle of the second century, when the Moors invaded Bética, up to the fourth century; the modifications that fear must have imposed on the population both urban and rural; and finally the spread of monasteries throughout the region with the new organisation of al1 the settlements and the ways of communication.